Continuous flat pressing surface layer flame-retardant shaving board and preparation method thereof

By pretreating the shavings and combining PAP-Mg-Zn as the surface flame retardant, the problems of poor uniformity of the flame retardant and insufficient interfacial compatibility in the prior art are solved, and the combustion performance and physical and mechanical properties of the flame retardant particle board are achieved, and the stability and quality of the product are improved.

CN119820670AActive Publication Date: 2025-04-15INST OF WOOD INDUDTRY CHINESE ACAD OF FORESTRY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510245431.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-04-15
Estimated Expiration
2045-03-03

AI Technical Summary

Technical Problem

In the existing continuous flat pressurized flame retardant particle board production process, the uniformity of the flame retardant and the surface shavings is poor, which makes it difficult to take into account both the combustion performance and physical and mechanical properties, and the interface compatibility between the flame retardant, adhesive and shavings is poor, affecting the quality of the panel.

Method used

The melamine-modified urea-formaldehyde resin adhesive and sodium hydroxide aqueous solution were used to pretreat the shavings, combined with PAP-Mg-Zn as the surface flame retardant, blended with the core shavings and then carried out continuous flat pressure treatment to make flame retardant particle board.

Benefits of technology

The combustion growth rate index of flame retardant particle board is reduced, the impact of flame retardant on the surface glue strength of particle board is reduced, the stability and interface compatibility of flame retardant are improved, and the quality and performance of the product are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119820670A_ABST
    Figure CN119820670A_ABST
Patent Text Reader

Abstract

According to the continuous flat pressing surface layer flame-retardant shaving board and the preparation method thereof, the combustion growth rate index of the flame-retardant shaving board can be reduced, and the influence of a flame retardant on the surface bonding strength of the shaving board is reduced. The method comprises the steps that raw material wood shavings are atomized at the same time, a melamine modified urea-formaldehyde resin adhesive with the mass accounting for 10-15% of the mass of the wood shavings and a sodium hydroxide aqueous solution with the mass accounting for 0.5-0.8% of the mass of the wood shavings and the concentration being 0.4-0.6 mol / L are applied, pretreated surface layer wood shavings are obtained, and the pretreated surface layer wood shavings and a surface layer flame retardant PAP-Mg-Zn are blended according to the mass ratio of 100: (15-17) to obtain flame-retardant surface layer wood shavings; after the flame-retardant surface layer wood shavings and the core layer wood shavings are laid in the mode that the surface layer wood shavings are located on the upper layer and the lower layer and the core layer wood shavings are located on the middle layer, continuous flat pressing treatment is conducted on a plate blank, the hot pressing speed is 220-250 mm / s, and therefore the continuous flat pressing surface layer flame-retardant shaving board is manufactured. Wherein the structural formula of PAP-Mg-Zn is shown in the specification. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of flame-retardant particleboards, and in particular to a continuous flat-pressed surface flame-retardant particleboard and a preparation method thereof. Background Art

[0002] The continuous flat-pressing production line has a fast production speed and high hot-pressing temperature, which places high demands on flame retardants and hot-pressing processes. The current conventional continuous flat-pressing flame-retardant particleboard production process has a large amount of surface flame retardant added, resulting in poor uniformity between the flame retardant and the surface particles, which makes it difficult to balance physical mechanics and combustion performance. At the same time, the interface compatibility between the flame retardant, adhesive and particles is poor, which causes the paving process to affect the surface quality of the slab, thus leading to product quality problems. Summary of the invention

[0003] The present invention is developed in view of the above problems, and its purpose is to provide a continuous flat-pressed surface flame-retardant particleboard and a preparation method thereof, which can reduce the combustion growth rate index of the flame-retardant particleboard and reduce the influence of the flame retardant on the surface bonding strength of the particleboard.

[0004] The first aspect relates to a method for preparing a continuously flat-pressed surface flame-retardant particleboard, comprising:

[0005] (1) A melamine-modified urea-formaldehyde resin adhesive at a weight of 10-15% by weight of the raw wood chips and a sodium hydroxide aqueous solution at a concentration of 0.4-0.6 mol / L at a weight of 0.5-0.8% by weight of the raw wood chips are simultaneously atomized to obtain pretreated surface wood chips, and the pretreated surface wood chips are blended with a surface flame retardant PAP-Mg-Zn at a mass ratio of 100:15-17 to obtain flame-retardant surface wood chips, wherein the PAP-Mg-Zn has a structural formula as follows.

[0006]

[0007] (2) applying a melamine-modified urea-formaldehyde resin adhesive to the raw wood chips by atomization to obtain core wood chips;

[0008] (3) The flame-retardant surface wood chips and the core wood chips are laid in a manner that the surface wood chips are in the upper and lower layers and the core wood chips are in the middle layer. After laying, the slabs are continuously flat-pressed, wherein the hot pressing temperature is 220-265° C., the hot pressing pressure is 2-2.5 MPa, and the hot pressing speed is 220-250 mm / s, thereby producing the continuous flat-pressed surface flame-retardant particleboard.

[0009] Wherein, the preparation of PAP-Mg-Zn is as follows:

[0010] 50-70 wt % of PAPEMP aqueous solution, 20-30 wt % of magnesium chloride aqueous solution and 20-40 wt % of zinc acetate solution are mixed in a ratio of 2:1:1-3, and stirred at a speed of 300-500 r / min for 25-30 min at room temperature to obtain a mixed solution containing a complexing primary product;

[0011] A 10-12 wt % NaOH aqueous solution is slowly added to the mixed solution at a mass ratio of 1:1-2.5 to promote the complexation reaction and the precipitation of the complex. The precipitated complex is filtered and dried to obtain PAP-Mg-Zn.

[0012] Wherein, step (2) comprises: applying 10-15% of the mass of the wood chips to the raw wood chips by atomization.

[0013] Wherein, in steps (1) and (2), the melamine-modified urea-formaldehyde resin adhesive has a solid content of 58%, a pH value of 8.5, a molecular weight of less than 300, and a melamine content of 9.5%.

[0014] Among them, the moisture content of the raw wood shavings is 2.5-3.5%.

[0015] Wherein, in step (3), the paving mass ratio of the surface layer and the core layer is 1:3.

[0016] The second aspect relates to a continuous flat-pressed surface flame-retardant particleboard prepared by the above-mentioned preparation method.

[0017] According to the present invention, the combustion growth rate index of the flame retardant particle board can be reduced, and the influence of the flame retardant on the surface bonding strength of the particle board can be reduced.

[0018] PAPEMP and metal ions simultaneously exhibit flame retardant properties, and form flame retardants through the complexation of lone electron pairs, which overcomes the heat energy consumed by the coordination bond energy during combustion and improves the flame retardant effect. In addition, during the combustion process, the metal active sites catalyze the dehydration of P-OH and wood materials / melamine-modified urea-formaldehyde resin under high temperature, promote the formation of POC cross-linked structure, and improve the carbonization rate.

[0019] The activity of the P-OH functional group is enhanced after catalysis by Mg / Zn metal ions, which in turn promotes the hydroxymethyl reaction between P-OH and the adhesive, allowing it to participate in the curing and cross-linking process of melamine-modified urea-formaldehyde resin from polymers with a molecular weight of less than 300, thereby increasing the cross-linking degree of the adhesive and reducing the negative impact of the addition of flame retardants on the curing process of the adhesive, thereby reducing the impact on the mechanical properties.

[0020] According to the present invention, the flame retardant may undergo a reverse reaction after synthesis. After synthesis, it is only filtered without washing, and a sodium hydroxide aqueous solution is further added in atomization during the pretreatment process to ensure that the complex flame retardant does not undergo a reverse reaction, thereby improving the stability of the flame retardant.

[0021] In addition, the amount of sodium hydroxide aqueous solution is controlled to be appropriate so that it penetrates into the surface of the wood chips, increases the moisture content of the wood chips, increases the activity of the hydroxyl groups in the chemical structure of the wood chips, and makes them closer to the polarity of the phosphorus hydroxyl groups in the flame retardant, thereby improving the interfacial compatibility between the flame retardant and the wood chips. At the same time, the hot pressing speed is controlled to ensure that the flame retardant does not absorb water on a large scale with the alkaline solution within a reasonable time to cause agglomeration. DETAILED DESCRIPTION

[0022] raw material:

[0023] 1. Melamine modified urea-formaldehyde resin adhesive

[0024] Solid content 58%, pH value 8.5, molecular weight less than 300, melamine content 9.5%

[0025] Purchased from: Guangzhou Yuanye Industrial Co., Ltd., model: DY103

[0026] 2. Bimetallic organic framework flame retardant PAP-Mg-Zn

[0027] Prepared by the following steps:

[0028] 50wt%-70wt% PAPEMP aqueous solution, 20wt%-30wt% magnesium chloride aqueous solution and 20wt%-40wt% zinc acetate solution are mixed in a ratio of 2:1:1-3, and stirred at a speed of 300-500r / min for 25-30min at room temperature to obtain a mixed solution containing a complex initial product; 10-12wt% NaOH aqueous solution is slowly added to the mixed solution, wherein the mass ratio of the alkaline solution to the mixed solution is 1:1-2.5, to promote the complex reaction and the precipitation of the complex, and the precipitated complex is filtered and dried in a 60-70°C forced air drying oven to obtain the bimetallic organic framework flame retardant, and its structural formula is as follows.

[0029]

[0030] Embodiment 1:

[0031] 1. Preparation of surface flame retardant bimetallic organic framework flame retardant:

[0032] First, 100g PAPEMP (polyamino polyether methylene phosphonic acid) was dissolved in 100g deionized water to prepare a 50wt% PAP solution; 100g MgCl2 was dissolved in 400g deionized water to prepare a 20wt% MgCl2 metal salt solution; 100g zinc acetate was dissolved in 400g deionized water to prepare a 20wt% zinc acetate solution; 100g NaOH was dissolved in 900g deionized water to prepare a 10wt% alkaline solution. Afterwards, the PAP solution, MgCl2 solution and zinc acetate solution were blended in a mass ratio of 2:1:1, and stirred at a speed of 300r / min for 30min at 25 degrees Celsius to obtain a mixed solution containing the initial complex product. Next, the alkaline solution was slowly added to the mixed solution (the mass ratio of the alkaline solution to the mixed solution was 1:1) to promote the complex reaction and the precipitation of the complex. Finally, the precipitated complex was filtered out and dried in a 60° C. forced air drying oven for 24 hours to obtain the final bimetallic organic framework flame retardant PAP-Mg-Zn.

[0033] 2. Particle pretreatment and preparation of flame retardant particleboard

[0034] The moisture content of eucalyptus wood shavings (30mm*2mm*0.14mm) was dried to 2.5%; the shavings were placed in a spray pipe and a melamine-modified urea-formaldehyde resin adhesive of 10% by weight of the shavings and a 0.5 mol / L sodium hydroxide aqueous solution of 0.5% by weight of the shavings were simultaneously atomized through a spray gun to obtain pre-treated surface shavings with a moisture content of 8.5%. The shavings were blended with a surface flame retardant PAP-Mg-Zn, and the amount of the surface flame retardant added was 15% of the weight of the pre-treated surface shavings to obtain flame-retardant surface shavings.

[0035] The moisture content of eucalyptus wood chips (30mm*2mm*0.14mm) is dried to 3.0%; the wood chips are placed in a spray pipe and a melamine-modified urea-formaldehyde resin adhesive of 7.5% by weight of the wood chips is applied by a spray gun to obtain a sizing-treated core layer wood chips.

[0036] Next, the flame-retardant surface shavings and core shavings are passed through the air paving machine, first paving the lower surface shavings, then paving the lower core shavings, upper core shavings and upper surface shavings in sequence, with the surface and core shavings paving mass ratio of 1:3. After completion, the slab is immediately subjected to a continuous flat pressing process, with a hot pressing temperature of 245°C, a hot pressing pressure of 2.5MPa, and a hot pressing speed of 250mm / s, thereby producing a 18mm thick layered flame-retardant particleboard.

[0037] performance:

[0038] 1. Combustion growth rate index peak: 1.01kW / m 2 . s, which is 30.3% lower than that of ordinary particleboard.

[0039] 2. Surface bonding strength: 1.1MPa.

[0040] Embodiment 2:

[0041] 1. Preparation of surface flame retardant bimetallic organic framework flame retardant:

[0042] First, 100g PAPEMP (polyamino polyether methylene phosphonic acid) was dissolved in 66g deionized water to prepare a 60wt% PAP solution; 100g MgCl2 was dissolved in 233g deionized water to prepare a 30wt% MgCl2 metal salt solution; 100g zinc acetate was dissolved in 150g deionized water to prepare a 40wt% zinc acetate solution; 100g NaOH was dissolved in 900g deionized water to prepare a 10wt% alkaline solution. After that, the PAP solution, MgCl2 solution and zinc acetate solution were blended in a mass ratio of 2:1:3, and stirred at a speed of 500r / min for 20min at 22 degrees Celsius to obtain a mixed solution containing the initial complex product. Next, the alkaline solution was slowly added to the mixed solution (the mass ratio of the alkaline solution to the mixed solution was 1:2.5) to promote the complex reaction and the precipitation of the complex. Finally, the precipitated complex was filtered out and dried in a forced air drying oven at 70° C. for 30 hours to obtain the final bimetallic organic framework flame retardant PAP-Mg-Zn.

[0043] 2. Particle pretreatment and preparation of flame retardant particleboard

[0044] The moisture content of poplar wood shavings (25mm*2.5mm*0.18mm) was dried to 3.5%; the shavings were placed in a spray pipe and a melamine-modified urea-formaldehyde resin adhesive of 15% by weight of the shavings and a 0.5 mol / L sodium hydroxide aqueous solution of 0.8% by weight of the shavings were simultaneously atomized through a spray gun to obtain pre-treated surface shavings with a moisture content of 8.3%. The shavings were blended with a surface flame retardant PAP-Mg-Zn, and the amount of the surface flame retardant added was 17% of the weight of the pre-treated surface shavings to obtain flame-retardant surface shavings.

[0045] The moisture content of dried poplar wood shavings (25mm*2.5mm*0.18mm) is reduced to 3.5%; the shavings are placed in a spray pipe and a melamine-modified urea-formaldehyde resin adhesive of 7.5% by weight of the shavings is applied by a spray gun to obtain sizing-treated core shavings.

[0046] Next, the flame-retardant surface shavings and core shavings are passed through the air paving machine, first paving the lower surface shavings, then paving the core layer (single layer) shavings and the upper surface shavings in sequence, with the surface layer and core layer paving mass ratio of 1:3. After completion, the slab is immediately subjected to a continuous flat pressing process. The hot pressing temperature is 245°C, the hot pressing pressure is 2MPa, and the hot pressing speed is 220mm / s, thereby producing a 18mm thick layered flame-retardant particleboard.

[0047] performance:

[0048] 1. Combustion growth rate index peak: 0.97kW / m 2 .s, which is 33.1% lower than that of ordinary particleboard.

[0049] 2. Surface bonding strength: 0.97MPa.

[0050] Comparative Example 1:

[0051] Except that the NaOH aqueous solution is not applied in the atomization treatment of the surface wood chips in step 2, the other steps are the same as those in Example 1.

[0052] performance:

[0053] 1. Combustion growth rate index peak: 1.23kW / m 2 .s, which is 15.2% lower than that of ordinary particleboard.

[0054] 2. Surface bonding strength: 0.40MPa.

[0055] Comparative Example 2:

[0056] Except that the precipitated complex in step 1 was filtered and then washed 5 times, the other steps were the same as those in Example 1.

[0057] performance:

[0058] 1. Combustion growth rate index peak: 1.16kW / m 2 .s, which is 19.6% lower than that of ordinary particleboard.

[0059] 2. Surface bonding strength: 0.69MPa.

[0060] Comparative Example 3:

[0061] Except for the step 2 in which the surface wood chips are atomized and the NaOH aqueous solution is applied in a ratio of 0.3% by weight of the wood chips, the other steps are the same as those in Example 1.

[0062] performance:

[0063] 1. Combustion growth rate index peak value: 1.05kW / m 2 .s, which is 27.6% lower than that of ordinary particleboard.

[0064] 2. Surface bonding strength: 0.54MPa.

[0065] Comparative Example 4:

[0066] Except that the flame retardant preparation PAPEMP in step 1 is not complexed with metal elements, the other steps are the same as those in Example 1. The surface flame retardant is prepared as follows:

[0067] 100 g of PAPEMP, 50 g of MgCl2 aqueous solution and 50 g of zinc acetate were mixed to obtain a surface flame retardant.

[0068] performance:

[0069] 1. Combustion growth rate index peak: 1.41kW / m 2 . s, 2.8% lower than ordinary particleboard

[0070] 2. Surface bonding strength: 0.47MPa

[0071] Comparative Example 5:

[0072] Except that the hot pressing speed of the hot pressing process in step 2 is 200 mm / s, the other steps are the same as those in Example 1.

[0073] performance:

[0074] 1. Combustion growth rate index peak value: 1.18kW / m 2 . s, which is 18.6% lower than that of ordinary particleboard.

[0075] 2. Surface bonding strength: 0.59MPa.

Claims

1. A method for preparing a continuous flat-pressed surface flame-retardant particleboard, It is characterized in that include: (1) A melamine-modified urea-formaldehyde resin adhesive of 10-15% by weight of the raw wood chips and a sodium hydroxide aqueous solution of 0.4-0.6 mol / L of 0.5-0.8% by weight of the raw wood chips are simultaneously atomized to obtain pretreated surface wood chips, and the pretreated surface wood chips are blended with a surface flame retardant PAP-Mg-Zn at a mass ratio of 100:15-17 to obtain flame-retardant surface wood chips, wherein the PAP-Mg-Zn structural formula is as follows: (2) applying a melamine-modified urea-formaldehyde resin adhesive to the raw wood chips by atomization to obtain core wood chips; (3) The flame-retardant surface wood chips and the core wood chips are laid in a manner that the surface wood chips are in the upper and lower layers and the core wood chips are in the middle layer. After laying, the slabs are continuously flat-pressed, wherein the hot pressing temperature is 220-265° C., the hot pressing pressure is 2-2.5 MPa, and the hot pressing speed is 220-250 mm / s, thereby producing the continuous flat-pressed surface flame-retardant particleboard.

2. The preparation method according to claim 1, wherein The preparation of PAP-Mg-Zn is as follows: 50-70 wt % of PAPEMP aqueous solution, 20-30 wt % of magnesium chloride aqueous solution and 20-40 wt % of zinc acetate solution are mixed in a ratio of 2:1:1-3, and stirred at a speed of 300-500 r / min for 25-30 min at room temperature to obtain a mixed solution containing a complexing primary product; A 10-12 wt % NaOH aqueous solution is slowly added to the mixed solution at a mass ratio of 1:1-2.5 to promote the complexation reaction and the precipitation of the complex. The precipitated complex is filtered and dried to obtain PAP-Mg-Zn.

3. The preparation method according to claim 1, wherein Step (2) comprises: A melamine-modified urea-formaldehyde resin adhesive in an amount of 10-15% by weight of the wood chips is atomized and applied to the raw wood chips.

4. The preparation method according to claim 1 or 3, wherein In steps (1) and (2), the melamine-modified urea-formaldehyde resin adhesive has a solid content of 58%, a pH value of 8.5, a molecular weight of less than 300, and a melamine content of 9.5%.

5. The preparation method according to claim 1, wherein The moisture content of the raw wood shavings is 2.5-3.5%.

6. The preparation method according to claim 1, wherein In step (3), the paving mass ratio of the surface layer and the core layer is 1:

3.

7. A continuous flat-pressed surface flame-retardant particleboard prepared by the preparation method according to claim 1.

Citation Information

Patent Citations

  • Method for manufacturing fire-retardant particleboard through continuous flat pressing

    CN110405898A

  • Preparation method of water-resistant flame-retardant particle board

    CN111844342A

  • Preparation method of flame-retardant shaving board and flame-retardant shaving board

    CN112829037A

  • Organic-inorganic hybrid boron-nitrogen-phosphorus ternary flame-retardant shaving board and preparation method thereof

    CN115229926A